ANALISIS KINERJA KEPALA DESA DALAM MEWUJUDKAN GOOD GOVERNANCE (Studi di Desa Pernek Kecamatan Moyo Hulu) - Ramdani, Arsa; Astikaningsih, Yuli; Diantari, Milan (Pusat Riset dan Publikasi, 2025)
This study research aims to explain the analysis of the performance of the head of Pernek village in realizing good governance based on the principles of Good Governance according to UNDP (United Nation Development Programme), 1997, namely (1) participation, (2) policy transparency, (3) accountability transparency, (4) development effectiveness, (5) law enforcement, (6) equality of service, (7) strategic vision of village heads, (8)responsiviness to complaints. These principles are inherent in a government in order to achieve what is expected so that good relations with the community can be felt. This study uses a qualitative research approach, by presenting the findings and conclusions of the analysis using a case study design. The informant of this study is the head of Pernek village, namely, Mr. Abdul Majid, A.Md. Data collection techniques are: in-depth interviews and direct observation at the research location. With the results of the research found, namely the Head of Pernek Village, explained community participation in village development through the mechanism of LKD, religious leaders, and community leaders for Musrenbangdus and Musrenbangdes. This community participation mechanism is designed to ensure that development is carried out from the bottom up, starting from the hamlet to the village level, involving various institutions and community stakeholders. This aims to create development planning that is more democratic, transparent, and aligned with the real needs of the community.